2010
DOI: 10.1016/j.virol.2009.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Elevated temperature triggers human respiratory syncytial virus F protein six-helix bundle formation

Abstract: Human respiratory syncytial virus (RSV) is a major cause of severe lower respiratory tract infection in infants, immunocompromised patients, and the elderly. The RSV fusion (F) protein mediates fusion of the viral envelope with the target cell membrane during virus entry and is a primary target for antiviral drug and vaccine development. The F protein contains two heptad repeat regions, HR1 and HR2. Peptides corresponding to these regions form a six-helix bundle structure that is thought to play a critical rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 64 publications
1
31
0
1
Order By: Relevance
“…The addition of heat has been reported to be a surrogate trigger for many full-length paramyxovirus fusion proteins (11,29,34,42,45). The mechanism probably involves thermal destabilization of the metastable F protein, initiating its conformational change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of heat has been reported to be a surrogate trigger for many full-length paramyxovirus fusion proteins (11,29,34,42,45). The mechanism probably involves thermal destabilization of the metastable F protein, initiating its conformational change.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism probably involves thermal destabilization of the metastable F protein, initiating its conformational change. Yunis et al (45) found that heating RSVinfected cells to 45 to 55°C enhanced antibody recognition of the membrane-anchored F protein by antiserum specific for the posttriggered 6-HB structure, indicating that elevated temperature can act as a surrogate trigger for the transmembrane RSV F protein. Raising the temperature to 60°C has also been shown to act as a surrogate trigger for the PIV5 sF protein, resulting in liposome association (11).…”
Section: Discussionmentioning
confidence: 99%
“…This refolding can also occur spontaneously on virions and cell surfaces 11 , and it can be stimulated with heat 12 , indicating that prefusion RSV F is metastable. During the refolding, the hydrophobic fusion peptide at the N terminus of the F 1 subunit pulls out from the central cavity of the prefusion trimer and inserts into the host-cell membrane 7 .…”
mentioning
confidence: 98%
“…This transition is irreversible under physiological conditions and renders the fusion protein inactive. Heat, low-molarity buffer, and freeze-thaw cycles have all been shown to cause this unidirectional conformation change (17,19,20). Recently, a number of conformation-specific antibodies have been characterized.…”
Section: Fig 2 Expression and Processing Of Hrc Mutations Transientlmentioning
confidence: 99%